Revisiting China’s Sponge City Planning Approach: Lessons From a Case Study on Qinhuai District, Nanjing - Chen, Shiyang; van de Ven, Frans H. M.; Zevenbergen, Chris; Verbeeck, Simon; Ye, Qinghua; Zhang, Weijun; Wei, Liang (Frontiers in Environmental Science, 2021)
Integrating sustainable urban water management into the urban planning process is essential for developing water-resilient cities. To this end, the central government of the People’s Republic of China initiated the ‘Sponge City’ programme. However, challenges and gaps exist in current urban planning practice. The operationalizable planning approach to realise the multiple objectives of Sponge City is missing in the existing guidelines. Using a local example of Sponge City planning in Nanjing City as a case study, this paper outlines the current Sponge City approach from the perspectives of planning content and planning process. A qualitative comparative analysis between Nanjing’s Sponge City planning and Auckland Water Sensitive Design, as well as an evaluation of the Sponge City approach through the lens of Dutch urban water management, identified key missing elements that would enhance the current Sponge City planning approach. Examples include targets for pluvial flood protection, a strategy for planning interventions, and tools for interdisciplinary cooperation in the planning process. This enhanced approach was successfully applied in the Sponge City planning for Qinhuai District, Nanjing City. Nevertheless, challenges on data availability and the decision-makers’ mindsets called for more efforts on the interface of research and policy development for upscaling the Sponge City approach.